Analisis Penggunaan Kamus Online Al-Ma’any untuk Pengembangan Kosakata Mahasiswa Pendidikan Bahasa Arab di Universitas Islam Negeri Sumatera Utara Medan - Lisa Rahmadhani Siregar; Robby Reyhan Chandra; Sari Annisa Siregar; Sahkholid Nasution (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to analyze the use of the Al-Ma’any Online Dictionary in supporting the development of Arabic vocabulary mastery among students in PBA 2 class at UIN Sumatera Utara. The primary issue observed among students is the lack of optimal utilization of the online dictionary due to certain challenges in its usage. The focus of this research is to explore how students utilize the online dictionary to enrich their vocabulary and its impact on their Arabic language proficiency. This study employs a qualitative approach with a descriptive design. Data were collected through interviews with students, observations of dictionary usage, and analysis of student assignments. The findings indicate that the Al-Ma’any Online Dictionary is effective in helping students expand their vocabulary, particularly in discovering word meanings and their usage in various contexts. However, some challenges were identified, such as limited understanding of subtle word meanings and dependency on internet connectivity. This study suggests that vocabulary development through the use of online dictionaries can be optimized by providing guidance and further training for students in utilizing the dictionary's features more comprehensively.